Efforts to Improve Alley Reading Skills Using Image Media in Class 1 Students - Indrawati, Reni Sukma (Universitas Sebelas Maret, 2020)
Language is an important component in everyday life. Through language, a person can communicate with other people, so that relationships between people can be well established. In addition, language can also show a person's personality and even a nation. Most members of society assume that people who are polite in language must have a good personality too, and vice versa. This study aims to improve reading aloud skills using image media. This study uses the spiral model PTK method from Kemmis and Taggart. From this research, the results show that students' reading aloud skills can improve with picture media.